Avaliação do comportamento de degradação de Blenda de PEBD com aditivo PEPZYME(TM) - Miranda, Gabriela Messias (2017)
Low density polyethylene (LDPE) was mixed with the PEPZYMETM commercial additive in order to prepare a blend with biodegradation behavior, therefore was added 8% of the commercial additive (PE8), once that the PE is a material of high resistance to degradation. Due to this property, processability and low cost, LDPE is a plastic very used in various applications, mostly in packaging. Beside biodegradation, it is important evaluate your abiotic degradation. For that, it was realized a accelerated aging assay for 1000 h with cycles of 8h of UVA radiation in 60 ºC and cycles of 4 h of condensation in 50 ºC, to evaluate the behavior of this material front weathering. After the pure PE samples (PE0) and with additive were removed to each 200h and characterized, in order to identify the changes in the chemical properties, physical, mechanical, thermal and morphological, caused through the additive effect as well as weathering effect. The results of this study showed that the aging provoke changes in the structural characteristics (insertion of functional groups) and morphological (appearance of microcracks and increase of th roughness), mechanical (increase of the stiffness and loss of plasticity) and thermal (increase of the crystallinity degree and of the range of thermal degradation) properties; being this changes very attractive for the microorganisms when the exposed materials were put in contact with the soil. The presence of the additive in the PE matrix helped in the aging process, once that functional groups were added in the chemical structure of LDPE. The C, H, N contents and carbonyl indexes of the samples were of according with the FTIR spectrums. The C:N ratios of PE8 and PE8/env presented the expected behavior in the literature (decrease of this value) for the occurrence of decomposition process.